Multimodal impact of copper-silicon hybrid nanotools towards bacterial leaf streak, wheat biochemistry and productivity parameters - Waqas Ahmad; Muhammad Atiq; Nasir Ahmed Rajput; Rizwana Maqbool; Jamil Shafi; Abdul Jabbar; Sohail Asad; Muhammad Jahanzaib Matloob; Hassan Zia; Muhammad Usama (PLoS ONE, 2025)
Wheat production is substantially harmed by biotic and abiotic stress. Among biotic stresses, bacterial leaf streak (BLS) of wheat caused by bacterium Xanthomonas translucens pv. undulosa (Xtu) induces crop yield losses up to 10–40%. This multi-step investigation encompassed the evaluation of the antibacterial potency of parthenium-mediated copper nanoparticles (CuNPs) and silicon nanoparticles (SiNPs). Green synthesized Cu-Si nanoparticles were evaluated under lab and greenhouse conditions employing a Complete Randomized Design (CRD) and under field conditions adopting Randomized Complete Block Design (RCBD) alone and in combination. The scanning electron microscopy and X-ray diffraction showed that CuNPs and SiNPs exhibited semi-spherical and spherical morphology with average size of 61.49nm and 14.36nm, respectively. Among the tested nanoparticles, maximal inhibition one was expressed by CuNPs + SiNPs (19.06 mm), followed by CuNPs (14.14 mm) and SiNPs (10.56 mm) as compared to control. The least disease incidence under greenhouse (14.75%) and field-scale evaluation (29.46%) was expressed by combined treatment CuNPs + SiNPs, followed by single treatment CuNPs and SiNPs in comparison with control. Moreover, the execution of the most effective dosage of CuNPs + SiNPs enhanced the amounts of enzymatic and non-enzymatic antioxidants like SOD, POD, CAT, H2O2, TPC, TSS by 3.09, 3.01, 1.87, 7.35, 3.61 and 1.08 µg/g, respectively. Similarly, most effective dosage of CuNPs + SiNPs increased the yield-related attributes of the wheat plant such as root length (4.52 cm), shoot length (4.063 cm), chlorophyll contents (5.56 SPAD), spike length (15.98 cm), spikelets per spike (19.88) and Number of grains per spike (31.97), 100 grains weight (17.07 g), plant height (81.46 cm), stomatal conductance (288.69 m.mol m−2s−1), and root biomass (492.15 kg/ha). Recent findings emphasize the potential of ecological nanotechnology-based tactics in plant disease management. Furthermore, nanoparticles applications with CuNPs and SiNPs were an eco-friendly tactic for managing the bacterial leaf streak of wheat and enhancing the antioxidant defense system and yield-related attributes of wheat.